Efficient unified architecture for post-quantum cryptography: combining Dilithium and Kyber - Patrik Dobias; Lukas Malina; Jan Hajny (PeerJ Computer Science)
As the ongoing standardization process of post-quantum schemes yields initial outcomes, it becomes increasingly important to not only optimize standalone implementations but also explore the potential of combining multiple schemes into a single, unified architecture. In this article, we investigate the combination of two National Institute of Standards and Technology (NIST)-selected schemes: the Dilithium digital signature scheme and the Kyber key encapsulation mechanism. We propose a novel set of optimization techniques for a unified hardware implementation of these leading post-quantum schemes, achieving a balanced approach between area efficiency and high performance. Our design demonstrates superior resource efficiency and performance compared to previously reported unified architecture (DOI 10.1109/TCSI.2022.3219555), also achieving results that are better than, or comparable, to those of standalone implementations. The efficient and combined implementation of lattice-based digital signatures and key establishment methods can be deployed for establishing secure sessions in high-speed communication networks at servers and gateways. Moreover, the unique and compact design that requires small hardware resources can be directly used in small and cost-effective field programmable gate array (FPGA) platforms that can be used as security co-processors for embedded devices and in the Internet of Things.